2012
DOI: 10.1177/0891242412452445
|View full text |Cite
|
Sign up to set email alerts
|

Employment Risk, Returns, and Entrepreneurship

Abstract: Comparing local employment portfolios against entrepreneurship, this research finds that local wage and salary job market prospects shape incentives for potential entrepreneurs. Entrepreneurship may thus be more attractive in areas featuring high employment risk and/or low returns. This research contributes to the existing regional employment portfolio literature by using more disaggregated data at both the county and the commuting zone levels. Commuting zones in particular represent a broader spectrum of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Many innovation-and opportunity-driven entrepreneurs do not envision hiring many employees, but entrepreneurs in personnel-intensive but low-risk businesses, such as retail or personal services, may foresee hiring more people (Delmar and Wiklund 2008). Opportunity-and innovation-oriented entrepreneurship tend to involve higher risks of failure compared with growth-oriented entrepreneurship since the former involve higher market uncertainty as they seek to turn new ideas into marketable products and services (Low and Weiler 2012). For growth-oriented entrepreneurship, on the other hand, market uncertainty is generally lower since most entrepreneurs in this category expect to employ at least five employees within a five-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many innovation-and opportunity-driven entrepreneurs do not envision hiring many employees, but entrepreneurs in personnel-intensive but low-risk businesses, such as retail or personal services, may foresee hiring more people (Delmar and Wiklund 2008). Opportunity-and innovation-oriented entrepreneurship tend to involve higher risks of failure compared with growth-oriented entrepreneurship since the former involve higher market uncertainty as they seek to turn new ideas into marketable products and services (Low and Weiler 2012). For growth-oriented entrepreneurship, on the other hand, market uncertainty is generally lower since most entrepreneurs in this category expect to employ at least five employees within a five-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Innovationoriented and opportunity-driven entrepreneurship are initiated by entrepreneurs seeking to turn new ideas into marketable products and services (Low and Weiler 2012). Such innovative entrepreneurs are often distinguishable from other entrepreneurs by their willingness to search and create new economic opportunities in the face of uncertainty and risk (Koellinger 2008;Wennekers and Thurik 1999).…”
Section: Insolvency Legislation Risk and Productive Entrepreneurshipmentioning
confidence: 99%
“…Low and Weiler (2012) explore the influence of local employment growth and volatility on subsequent self-employment and establishment birth rates, which is the converse of a question addressed here. Low and Weiler (2012) explore the influence of local employment growth and volatility on subsequent self-employment and establishment birth rates, which is the converse of a question addressed here.…”
Section: Literature Performance Measures and Hypothesesmentioning
confidence: 99%
“…In an analysis of returns to self‐employment, Evans and Leighton () found that entrepreneurs starting a new business, who had less formal education and a long period of unemployment prior to starting their business, were often less skilled than individuals doing the same job for either wage or salary income. Supporting this argument, Low and Weiler () found that limited employment prospects increased the likelihood of individuals opting to become entrepreneurs within regional commuting zones.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Prior U.S. entrepreneurial research has focused on regional growth in the number of self‐employed individuals rather than self‐employment income (Edmiston, ; Gallardo & Scammahorn, ; Henderson, ; Low & Weiler, ; Van Praag & Versloot, ), or on the relationship between the number of self‐employed individuals and various measures of regional economic activity (Acs, ; Bunten, Weiler, Thompson, & Zahran, ; Fleming & Goetz, ; Glaeser & Kerr, ; Low, ; McGranahan, Wojan, & Lambert, ). However, if entrepreneurs earn less than their salaried employment alternatives, increased entrepreneurship may not be an efficient regional development strategy.…”
Section: Introductionmentioning
confidence: 99%